2003
DOI: 10.4049/jimmunol.170.1.73
|View full text |Cite
|
Sign up to set email alerts
|

CD19 Function in Early and Late B Cell Development: I. Maintenance of Follicular and Marginal Zone B Cells Requires CD19-Dependent Survival Signals

Abstract: Loss of membrane-bound Ig results in the rapid onset of apoptosis in recirculating B cells. This observation implies that a competent B cell receptor (BCR) is not only required for Ag-dependent differentiation, but also for continued survival in the peripheral immune system. Expression of the B cell coreceptor, CD19, is likewise essential for key B cell differentiative events including the formation of B-1, germinal center, and marginal zone (MZ) B cells. In this study, we report that CD19 also exerts a role b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 59 publications
4
92
2
1
Order By: Relevance
“…In addition, we found that BAFF is required for normal CD21 expression in B cells and for the generation of marginal zone B cells. Importantly, a Bcl-2 transgene rescued the marginal zone B cell deficiency in CD19 -/-mice, ruling out the hypothesis that these cells could be unresponsive to Bcl-2 [33].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, we found that BAFF is required for normal CD21 expression in B cells and for the generation of marginal zone B cells. Importantly, a Bcl-2 transgene rescued the marginal zone B cell deficiency in CD19 -/-mice, ruling out the hypothesis that these cells could be unresponsive to Bcl-2 [33].…”
Section: Discussionmentioning
confidence: 98%
“…The balance between marginal zone versus follicular B cell development is also regulated by Aiolos and Btk [21], whereas CD19 is important for the survival and differentiation of several B cell populations, including B1 and marginal zone B cells [33]. Inactivation of the repressor activity of RBP-J by Notch signaling promotes marginal zone B cell formation, whereas the Notchantagonizing protein MINT prevents it [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that heparin is either recruiting coreceptors that can reduce the signaling threshold of the preBCR, or that heparin is modifying the cell surface milieu and allowing the antiAb to be more effective. These findings prompted us to compare the results when cells are pretreated with an activating, anti-CD19 Ab because CD19 has been reported to establish signaling thresholds of the preBCR (25)(26)(27)(28). Activating the CD19 pathway before anti-stimulation resulted in increased pERK levels, similar to when cells were pretreated with heparin.…”
Section: Heparin and Heparan Sulfate Increase Signaling Via The Prebcrmentioning
confidence: 97%
“…In fact, heparin or heparan sulfate in combination with anti-treatment of cells causes a similar response by pERK compared with anti-CD19 and anti-. Current models suggest CD19 lowers the threshold of activation of the preBCR and BCR, and establishes critical signaling thresholds (25)(26)(27)(28). In its absence, there is an impaired proB to preB cell transition and a severe reduction in mature B cells.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of CD19 on the cell surface is essential for B lymphocyte activation; under--expression of CD19 is associated with fewer peritoneal B cells, decreased B cell proliferative responses to mitogen, greatly reduced concentrations of serum immunoglobulin (Engel et al, 1995), decreased responses to T--cell--dependent B cell antigens, absent germinal center formation and afBinity maturation (Rickert et al, 1995). CD19 provides tonic survival signals to recirculating naive B lymphocytes; the B cell compartment in CD19 --/--mice can be partially rescued by over--expression of apoptosis survival genes (Otero et al, 2003).…”
Section: Cd19 -The Co-signaling Molecule Of Cr2mentioning
confidence: 99%